Training Surgeons to Perform Arthroscopic All-Inside Meniscal Repair: A Randomized Controlled Trial Evaluating the Effectiveness of a Novel Cognitive Task Analysis Teaching Tool, Imperial College London/University College London Meniscus Repair Cognitive Task Analysis (IUMeRCTA) - Karamchandani, Urvi; Bhattacharyya, Rahul; Patel, Rahul; Oussedik, Sam; Bhattacharya, Rajarshi; Gupte, Chinmay (American Journal of Sports Medicine, 2021)
Background: All-inside meniscal repair is an increasingly common technique for the surgical treatment of meniscal tears. There are currently no standardized techniques for training residents in this procedure. Cognitive task analysis (CTA) is a method of analyzing and standardizing key steps in a procedure that allows training to be conducted in a validated and reproducible manner. Purpose: (1) To design a digital CTA teaching tool for a standardized all-inside meniscal repair. (2) To evaluate whether CTA-trained residents would perform better in a meniscal repair task compared with a control group who underwent traditional apprenticeship methods of training. Study Design: Controlled laboratory study. Methods: Three expert knee surgeons were interviewed using a modified Delphi method to generate a consensus among the ideal technical steps, cognitive decision points, and common errors and solutions for an all-inside meniscal repair. This written information was then combined with visual and audio components and integrated onto a digital platform to create the Imperial College London/University College London Meniscus Repair Cognitive Task Analysis (IUMeRCTA) tool. Eighteen novice residents were randomized into an intervention group (digital CTA tool) and control group (equipment instruction manual). Both groups performed an all-inside meniscal repair on high-fidelity, phantom knee models and were assessed by expert surgeons, blinded to the interventions, using a validated global rating scale (GRS). After a power calculation, median GRS scores were compared between groups using the Mann-Whitney U test; significance was set at P <.05. Results: For the IUMeRCTA tool design, the procedure was divided into 55 steps across 9 phases: (1) preoperative planning, (2) theater and patient setup, (3) portal placement, (4) meniscal examination, (5) tear reduction, (6) suture planning, (7) suture insertion, (8) repair completion, and (9) postoperative care and rehabilitation. For the trial, the intervention group (mean ± SD GRS, 32 ± 2.9) performed significantly better than did the control group (GRS, 24 ± 3.3; P <.001). Conclusion: This is the first CTA tool to demonstrate objective benefits in training novices to perform an arthroscopic all-inside meniscal repair. Clinical Relevance: The IUMeRCTA tool is an easily accessible and effective adjunct to traditional teaching that enhances learning the all-inside meniscal repair for novice surgeons.